2021
DOI: 10.3390/su13041881
|View full text |Cite
|
Sign up to set email alerts
|

The Hydration, Mechanical, Autogenous Shrinkage, Durability, and Sustainability Properties of Cement–Limestone–Slag Ternary Composites

Abstract: This study examines the hydration–mechanical–autogenous shrinkage–durability–sustainability properties of ternary composites with limestone filler (LF) and ground-granulated blast furnace slag (BFS). Four mixtures were prepared with a water/binder ratio of 0.3 and different replacement ratios varying from 0 to 45%. Multiple experimental studies were performed at various ages. The experimental results are summarized as follows: (1) As the replacement levels increased, compressive strength and autogenous shrinka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…A noticeable acceleration of the alite reaction occurs, as indicated by the shortening of the induction phase, which can be seen in Figure 7 . Increased hydration rates of cements with limestone addition have also been noted by Zajac et al [ 49 ], Xuan et al [ 40 ], and Puerta-Falla [ 50 ].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…A noticeable acceleration of the alite reaction occurs, as indicated by the shortening of the induction phase, which can be seen in Figure 7 . Increased hydration rates of cements with limestone addition have also been noted by Zajac et al [ 49 ], Xuan et al [ 40 ], and Puerta-Falla [ 50 ].…”
Section: Resultssupporting
confidence: 59%
“…The range of limestone addition was set to 5–15%. Previous research [ 40 , 41 ], as well as previous tests by the authors [ 41 ], had shown that using more than 15% of limestone can greatly decrease the strength of mortars and concrete. Seeing as the assumption of undertaken research was to create and test cements that could be easily implemented in practice, the highest addition of limestone was set to 15%.…”
Section: Methodsmentioning
confidence: 98%
“…Fourth, based on the experimental results of this study, SAP can be used as a component of high-strength concrete which has a low water/binder ratio [37]. SAP can lower the AS of hardening high-strength concrete and mitigate cracks due to AS.…”
Section: Discussionmentioning
confidence: 84%
“…As shown in Figure 5, the development of AS can be divided into the following three stages: rapid growth period at initial ages, stable period at middle ages, and continuous growth period at later ages. There are five reasons for the change in AS: (i) cement hydration consumes water and the internal relative humidity decreases, resulting in a rapid increase in AS (shrinkage factor) [12]; (ii) the densification of the internal pore structure, resulting in increased AS (shrinkage factor) [33]; (iii) the pozzolanic reaction of silica fume and slag to produce dense C-S-H, as well as to promote AS development (i.e., shrinkage factor) [34]; (iv) the production of AFm and internal temperature changes leading to expansion (expansion factor) [35]; (V) limestone stabilizes the produced ettringite and causes expansion (expansion factor) [36,37]. The final macroresponse depends on changes in the dominant expansion and contraction factors.…”
Section: Autogenous Shrinkage (As) Coupled With Internal Relative Humidity and Temperaturementioning
confidence: 99%
“…Mineral additives, natural or byproduct materials, are widely used in blended cement systems to improve the chemical properties, i.e., hydration reactions, the mechanical properties such as strength, and the durability of concretes [9,10]. Among mineral additives used, ground granulated blast furnace slag (GGBFS), fly ash (FA), and limestone filler (LF) are the most commonly used for cement replacement.…”
Section: Introductionmentioning
confidence: 99%